Cerebral venous sinus thrombosis and exploration of prognostic factors: a case series - Liu, Jiahui; Yang, Junfeng; Fan, Yu; Jiang, Changchun (Frontiers in Neurology, 2024)
BackgroundThis study examined the etiology, treatment response, and prognosis of patients with cerebral venous sinus thrombosis (CVST) at a single institution.MethodsThis retrospective study included patients diagnosed with CVST between January 2016 and December 2020 at Baotou Central Hospital. The data were collected from patient charts, including sex, age, comorbidities, pregnancy, smoking, alcohol drinking, symptoms at onset, radiological location, examinations, Glasgow coma scale (GCS) at admission, National Institutes of Health stroke scale (NIHSS) at admission, modified Rankin scale (mRS) at admission, and treatments.ResultsThe study included 31 patients (13 males and 18 females) aged 39.0 (interquartile range, 30.0–53.0) years. Three (9.7%) patients had a history of hypertension, one (3.2%) had a history of stroke, four (12.9%) had thrombotic disorders, six (19.4%) were pregnant (including three who delivered), four (12.9%) were smoking, and four (12.9%) were drinking alcohol. The GCS at admission was 15.0 (IQR, 15.0–15.0), the NIHSS at admission was 0.0 (IQR, 0.0–2.0), and the mRS at admission was 0.0 (IQR, 0.0–0.0). The patients were grouped according to their mRS (>0 vs. 0); there were no significant differences between the two groups regarding the patient characteristics (all p > 0.05). Only an NIHSS of >0 at follow-up was associated with a 3-month mRS >0 (p < 0.001).ConclusionThe median age of the patients with CVST was 39 years. The majority were female (58%), 13% had thrombotic disorders, and 19% were or were recently pregnant. Only a NIHSS of >0 at follow-up was associated with a 3-month mRS >0.